Cardiometabolic Risk in Stunted Children: A Literature Study - Brigitte Sarah Renyoet; Ilmia Fahmi (Postgraduate, University of Mataram, 2025)
Global health and nutrition are undergoing an epidemiological transition with the emergence of the